Disjunction, oscillation, contagion: the visible and the enunciable in Jean-Luc Nancy - de la Higuera, Javier (Escritura e Imagen, 2019)
This article examines the problem of the relationship between the visible and the enunciable, image and text, in Jean-Luc Nancy’s thinking. To this end, the theoretical framework of this problem is first traced in what is called “the aesthetics of thought”, showing what displacement the French thinker introduces in the treatment of this problem regarding conventional aesthetics and its relationship, in this aspect, with other thinkers such as Blanchot, Derrida or Foucault. Secondly, it reconstructs the displacement that the visible/enunciable question suffers in Nancy’s reflection, from a mainly linguistic or gramatological interpretation to another, a more fundamental one, of an eminently figurative character. On this radical figurative plane, the arts and literature seem to take a second place to what Nancy calls “the art of making a world”.
Keywords: image; text; no-relation; arts; literature